2020
DOI: 10.1063/5.0015547
|View full text |Cite|
|
Sign up to set email alerts
|

Thermal evolution of ferroelectric behavior in epitaxial Hf0.5Zr0.5O2

Abstract: Herein we report a cryogenic-temperature study on the evolution of ferroelectric properties of epitaxial Hf0.5Zr0.5O2 thin films on silicon. Wake-up, endurance, and fatigue of these films are found to be intricately correlated, strongly hysteretic, and dependent on available thermal energy. Field-dependent measurements reveal a decrease in polarization with temperature, which has been determined not to be an intrinsic change of the material property, rather, a demonstration of the increase in the coercive bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…(Nfatig: number of cycles at Pfatig, Nwake: number of cycles at Pwake) which is fit to R(T) = Ae (-Ea/kT) (A: fitting constant, Ea: activation enrgy, k: Boltzmann constant) in order to obtain Ea. It is shown that the fatigued effect is accelerated with larger Vw (3.5 V) at elevated temperature from 300 K to 400 K. The extracted activation energy (Ea=42.97 meV) of Vw=3.5 V in the fatigue model [11] is approximately twice larger than of the smaller Vw (2.5 V) with Ea=23.67 meV, which is close to the previously reported Ea=23.4 meV in [11]. In Fig.…”
Section: Wake-up/fatigue Effects From 4 K To 400 Ksupporting
confidence: 85%
See 1 more Smart Citation
“…(Nfatig: number of cycles at Pfatig, Nwake: number of cycles at Pwake) which is fit to R(T) = Ae (-Ea/kT) (A: fitting constant, Ea: activation enrgy, k: Boltzmann constant) in order to obtain Ea. It is shown that the fatigued effect is accelerated with larger Vw (3.5 V) at elevated temperature from 300 K to 400 K. The extracted activation energy (Ea=42.97 meV) of Vw=3.5 V in the fatigue model [11] is approximately twice larger than of the smaller Vw (2.5 V) with Ea=23.67 meV, which is close to the previously reported Ea=23.4 meV in [11]. In Fig.…”
Section: Wake-up/fatigue Effects From 4 K To 400 Ksupporting
confidence: 85%
“…Note that the Pr is higher in the elevated temperature even in the initial state, possibly because that the PEALD HZO is already substantially woken-up (i.e., charges are evenly distributed) in the fresh cell, which is not the case in [12]. Similar trend was shown in [11] with epitaxially grown HZO which showed relatively less phase transition between ferroelectric phase and dielectric phase during the post-cycling process. In order to observe the accelerated wake-up/fatigue effects at deepcryogenic 4 K, the tp was increased from 2 µs to 100 µs in 2171 µm 2 capacitor in Fig.…”
Section: Wake-up/fatigue Effects From 4 K To 400 Ksupporting
confidence: 57%
“…In addition, thermally induced strain can also directly affect polarization rotation and wake‐up effects through complicated electromechanical coupling. [ 94 ]…”
Section: Epitaxial Hafnia Thin Filmmentioning
confidence: 99%
“…[ 92,93 ] In addition, the thermal expansion coefficient for HZO is about 3.7 × 10 −6 K −1 , 0.8 × 10 −6 K −1 , and 7.5 × 10 −6 K −1 for the a, b and c axis, separately. [ 94 ] The much smaller thermal expansion coefficient of Si makes hafnia thin films under in‐plane tensile strain during cooling, and thus causing contraction of the out‐of‐plane lattice parameter of the orthorhombic (111) HZO. [ 38 ] The thermal expansion coefficient mismatch between the substrate and HZO layers provides an added biaxial strain on hafnia (111) layers, stabilizing the polar phase at room temperature.…”
Section: Epitaxial Hafnia Thin Filmmentioning
confidence: 99%
“…It was reported that most of the polarization in the HZO(111) / LSMO(001) structures could be attributed to oxygen vacancy migration, 41 with the intrinsic ferroelectric polarization estimated to be less than 9 µC/cm 2 . In addition, it was reported that Pr in the 5.6-nm-thick HZO films grown on LSMO/LaNiO3/CeO2/YSZ/Si(100) decreases by a factor of 3 from 300 K to 20 K. 43 On the other hand, for the YHO(111) films studied in this work, Pr exhibits a large value at low temperature and stays nearly constant below 100 K. This suggests that the extrinsic contributions are minimal to the measured Pr at low temperature. The moderate overall change of Pr with temperature also indicates that the contribution from the intrinsic ferroelectricity dominates even at room temperature.…”
Section: Local Switching and Temperature Dependence Of Polarizationmentioning
confidence: 99%